Senology in gynaecology specialist training: a baseline survey from 2014 = Senologische Weiterbildung in der Gynäkologie : eine Bestandsaufnahme 2014 - Puppe, Julian; Schott, Sarah (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Qualified training in senology is essential for maintaining adequate, high quality patient care. In order to meet the needs of doctors in training and those of the medical infrastructure it is necessary to assess the quality of training regularly, to enable its adaption and optimisation. Methods: We developed a comprehensive, 10 item online questionnaire to assess the quality of specialised training in senology. This questionnaire was sent to 4000 speciality trainees and young specialists countrywide via the DGGG newsletter and was accessible for over four weeks. Results: 111 obstetrics and gynaecology speciality trainees participated in this national survey, 79 % of whom were female. 33 % of participants were working at university hospitals, 29 % at hospitals offering maximal level care without an associated medical faculty, 37 % at hospitals offering primary and secondary level care and 2 % at gynaecology practices. 25 % of participants could imagine working in the field of senology in future. On average the current perception of general specialist training was satisfactory. Specialist trainees at university hospitals rated training in senology highest (score: 2.95) compared to those at other hospitals. A fixed rotation through a breast centre offering comprehensive advanced training was seen as a potential improvement to senology training. Conclusions: This is the first survey of specialised training in senology to be conducted in Germany. Results showed that there is significant potential for young doctors to enter the speciality in future. There are also significant differences in the perceived quality of senology training between training facilities. This survey aimed to determine the quality of specialised training at senology centres and hopes to contribute to a sustainable improvement in training. The intention is to continue to make senology attractive to gynaecologists and to ensure well-grounded training.
Gesehen am 16.09.2019